Advanced techniques for quantum-state specific reaction dynamics of gas phase metal atoms - Xu, Ang; Ma, Yu-jie; Yan, Dong; Li, Fang-fang; Liu, Jia-xing; Wang, Feng-yan (Chinese journal of chemical physics, 2021)
One of the themes of modern molecular reaction dynamics is to characterize elementary chemical reactions from “quantum state to quantum state”, and the study of molecular reaction dynamics in excited states can help test the validity of modern chemical theories and provide methods to control chemical reactions. The subject of this review is to describe the recent experimental techniques used to study the reaction dynamics of metal atoms in the gas phase. Through these techniques, information such as the internal energy distribution and angular distribution of the nascent products or the three-dimensional stereodynamic reactivity can be obtained. In addition, by preparing metal atoms with specific excited electronic states or orbital arrangements, information about the reactivity of the electronic states enriches the relevant understanding of the electron transfer mechanism in metal reaction dynamics.